Ethnic disparities in Phyllodes Tumour in Aotearoa New Zealand: a retrospective review. Issue 3 (24th January 2022) - Grinlinton, Megan Elizabeth; McGuinness, Matthew James; Christie, Mary; Oldfield, Robyn; Ramsaroop, Reena; Moss, David
Abstract: Background: Phyllodes tumour (PT) is a rare breast neoplasm and little is known about its epidemiological risk factors. The literature suggests a higher incidence of PT in Asian patients and other minority ethnic groups. The purpose of this study was to identify whether there was a difference in incidence, grade and age at presentation for patients with PT among minority ethnic groups when compared with European patients in Aotearoa New Zealand (AoNZ). Methods: A retrospective review was conducted across the three District Health Boards (DHBs) in Auckland, Aotearoa New Zealand (AoNZ), from 2008 to 2018 to investigate the relationship between ethnicity and clinical characteristics of PT. Demographic information and histology reports were reviewed to obtain relevant data. The primary outcome measure was ethnicity and the secondary outcome measures were age at presentation, tumour volume and grade. Results: One hundred and fifty‐nine patients were included. The total number of non‐European patients were 108 (68%). Minority ethnic groups including Pasifika, Māori and MELAA were overrepresented in the patient cohort. Larger tumour volume was significantly correlated with higher tumour grade ( p  < 0.001). Pasifika patients presented with larger tumours ( p 0.05) and at a younger age ( p 0.027) when compared with European patients. Conclusion: This study found that patients with PT in AoNZ were significantly overrepresented in Asian, Pasifika and MELAA ethnic groups. Pasifika patients may be at an increased risk of presenting at a younger age with larger, higher grade tumours when compared with European patients. Further research is required to investigate the reasons behind these findings in minority ethnic groups. Abstract : PT is a rare breast neoplasm which is overrepresented in Pasifika/Asian/MELAA patients in Aotearoa New Zealand. This study found that Pasifika patients presented with larger tumours and at a younger age when compared with European patients. Pasifika patients with PT may represent a higher risk group in AoNZ when compared with other ethnicities, in particular European patients. This is the first known study documenting the demographic factors of patients with PT in AoNZ.